Karṇāṭaka-Jaina-kavi, arthāt, Kanarī bhāshāke 75 Jaina kaviyoṃkā saṅkshipta paricaya - Premī, Nāthūrāma, b. 1881 (SAMP early 20th-century Indian books project, 1914)
Short biography of 75 Jaina Kannada poets.